Customers’ Perception on QR Code Payment Transaction - Nurul Afiza Saila Mohd Sabri; Aliana Anum Aminuddin (CSR International Journal, 2023)
This study aims to explore people’s perceptions of QR code payment transactions in Kuantan. The questions were prepared using a quantitative descriptive method. The data were obtained through a Google Form. This research can be used as a reference for related parties to formulate the right strategy in increasing both the number of merchants and the use of QR for transactions in the new normal era to increase the use of digital payments and support the creation of a cashless society in Malaysia. This research shows that for question 1, 40% of the respondents answered neutral, and only 2% strongly disagreed. For question 2, This is stated by 44% of respondents answered strongly agree, and 2% strongly disagree. For question 3, the response for this particular question in the questionnaire was dominant, with which is 44% and only 6% of respondents strongly disagreed. Lastly, the majority of the respondents don’t mind using both QR codes and cash, with 36% of respondents agreeing and 0% choosing to disagree, respectively, with this statement.